(3GdTQYjI GdOhdjI aj Xd GdfXGe GdYGdej GdLOjOs - (3eMehO UGdM(B, (3GdYGOdjs ((3GdEScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s)
(3GdGee GdeJMOI heYWjGJ GdfXGe GdYGdej GdLOjO(B- (3GdYQhHI hGdESdGe hJMOjGJ GdfXGe GdYGdej GdLOjO(B- (3eMceI GdYOd GdYQHjI Hjf QhGSH GdeGVj hJWdYGJ GdeSJbHd(B.s
Keywords: (3GdSjGSI GdOhdjIs; (3GdTQYjI GdOhdjIs; (3GdbGfhf GdOhdjs; (3GdfXGe GdYGdej GdLOjOs